Interlocking nail treatment of long-bone fractures in cats: 33 cases (1995–2004) - Díaz-Bertrana, M. C.; Durall, I.; Puchol, J. L.; Sánchez, A.; Franch, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A retrospective study between 1995 and 2004 of fracture repair in cats (n=46) using interlocking nails (ILN) was made. Only the cases in which clinical and radiographic examination of bone healing were available are included. Five humeral and twenty eight femoral fractures were reviewed. Multiple-hole interlocking nails (MH-ILN) were used in 22 fractures, with the four-hole model (FH-ILN) in the remaining cases. In three of the cases, the FH-ILN was transformed to a three-hole model by cutting the nail between the two most distal holes. The average length of humeral ILN was 78.8 mm, and the femoral ILN was 97.2 mm. Static fixation was performed in 27 cases, with dynamic fixation in the remaining. The medullary canal filling was 100% in both radiographic views in 16 cases. Intra-operative complications were encountered in two cases. A total number of 76 screws were inserted, with 5.26% of them being malpositioned. Malunion, in a deformed femur, and partial unscrewing of one screw were the only radiographic complications observed at the time of follow-up. The clinical outcome, as well as fracture healing, were excellent in all of the cases. The results of this study indicate that the 4.0 and 5.0 mm MH-ILN and FH-ILN can be used to repair simple or comminuted humeral and femoral fractures in cats.
Keywords: Interlocking nail; femoral; humeral; fracture; cats